Pyrene‐Based Dopant‐Free Hole‐Transport Polymers with Fluorine‐Induced Favorable Molecular Stacking Enable Efficient Perovskite Solar Cells. Issue 24 (12th April 2022) - Yao, Zhaoyang; Zhang, Fuguo; He, Lanlan; Bi, Xingqi; Guo, Yaxiao; Guo, Yu; Wang, Linqin; Wan, Xiangjian; Chen, Yongsheng; Sun, Licheng
Abstract: A new class of polymeric hole‐transport materials (HTMs) are explored by inserting a two‐dimensionally conjugated fluoro‐substituted pyrene into thiophene and selenophene polymeric chains. The broad conjugated plane of pyrene and "Lewis soft" selenium atoms not only enhance the π–π stacking of HTM molecules greatly but also render a strong interaction with the perovskite surface, leading to an efficient charge transport/transfer in both the HTM layer and the perovskite/HTM interface. Note that fluorine substitution adjacent to pyrene boosts the stacking of HTMs towards a more favorable face‐on orientation, further facilitating the efficient charge transport. As a result, perovskite solar cells (PSCs) employing PE10 as dopant‐free HTM afford an excellent efficiency of 22.3 % and the dramatically enhanced device longevity, qualifying it among the best PSCs based on dopant‐free HTMs. Abstract : A new class of polymeric hole‐transport materials (HTMs) was explored, featuring fluorine‐substituted pyrene and specific Pb−Se secondary interactions. Perovskite solar cells (PSCs) using PE10 as dopant‐free HTM, afforded an excellent PCE of 22.3 %, positioning it among the best PSCs based on dopant‐free HTMs.